(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article, regarding one of the most crucial, valuable, and historical work of turkic literature world, discusses the fate of the book “Devonu Lugotit-Turk” by Mahmood Koshghariy: translations, the time until the book is delivered to readers.